Analisis faktor-faktor yang mempengaruhi tingkat pembiayaan murabahah pada Bank Umum Syariah di Indonesia - Listiyaniningsih, Listiyaniningsih; Bawono, Anton (Journal of Accounting and Digital Finance, 2021)
This study aims to determine the effect of CAR, NPF, Equity, and Bank Indonesia Syariah Certificates (SBIS) on Murabahah Financing moderated by TPF at Islamic Commercial Banks in 2016-2020. This research is a type of quantitative research. The population in this study was 14 Indonesian Islamic Commercial Banks, with the sampling technique being purposive sampling. The sample used as the object of research is 11 Islamic banks. The method used in this research is Moderated Regression Analysis (MRA). The results of this study indicate that the CAR, NPF, and Equity variables do not affect Murabahah Financing, and SBIS affects Murabahah Financing. Then based on the results of the MRA test, it was found that TPF was unable to moderate the effect of CAR, NPF, Equity on Murabahah Financing. However, DPK was able to moderate the influence of SBIS on Murabahah Financing.